Self-guided Langevin dynamics study of regulatory interactions in NtrC - Damjanović, Ana (2009)
Multiple self-guided Langevin dynamics (SGLD) simulations were performed to examine structural and dynamical properties of the receiver domain of Nitrogen Regulatory Protein C (NtrC(r)). SGLD and MD simulations of the phosphorylated active form structure suggest a mostly stable but broad structural ensemble of this protein. The finite difference Poisson-Boltzmann calculations of the pK(a) values of the active site residues suggest an increase in the pK(a) of His-84 upon phosphorylation of Asp-54. In SGLD simulations of the phosphorylated active form with charged His-84 the average position of the regulatory helix α4 is found closer to the starting structure than in simulations with the neutral His-84. To model the transition pathway the phosphate group was removed from the simulations. After 7 ns of simulations, the regulatory helix α4 was found approximately halfway between positions in the NMR structures of the active and inactive forms. Removal of the phosphate group stimulated loss of helix α4, suggesting that the pathway of conformational transition may involve partial unfolding mechanism. The study illustrates the potential utility of the SGLD method in studies of the coupling between ligand binding and conformational transitions.